Endoscopic Removal of Multiple Toothbrushes: A Case Report - Young Woo Chae; Ilsoo Kim; Woon Geon Shin (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Foreign body ingestion is a common emergency that necessitates endoscopic intervention. Although many foreign bodies are easily removed, removal of magnets, blades, barbs, and unusually shaped objects, such as toothbrushes is challenging. Toothbrush ingestion may potentially cause complications such as pressure ulcers and perforations. We present a rare case of a 26-year-old woman with schizophrenia, who ingested multiple foreign bodies but was asymptomatic. Radiography showed multiple toothbrushes in the stomach. Emergency non-sedated endoscopy revealed eight toothbrushes in the stomach; five toothbrushes lodged in the great curvature of the stomach and three in the duodenal bulb were successfully removed using a snare and a technique that involved neck hyperextension to facilitate passage. This report describes a case of non-sedated endoscopic removal of multiple toothbrushes, which is rarely reported in the literature. This case highlights that even complex foreign bodies can be safely removed via endoscopy without surgical intervention. To our knowledge, this is the first report in the English literature that discusses endoscopic removal of more than five toothbrushes and underscores the role of customized approaches in the management of ingestion of unusual foreign bodies.